Harnessing Artificial Intelligence in Language Acquisition: Perceptions and Experiences of BIPA Learners in the Digital Era - Rani Siti Fitriani; Mohd Saleem Bhat; Muhamad Arif (JURNAL TEKNOSAINS KODEPENA, 2025)
The development of artificial intelligence (AI) technology has transformed the landscape of language education, including the learning of Indonesian forForeign Speakers (BIPA). This study aims to analyze the perceptions andexperiences of BIPA learners in using AI-based platforms as a medium for selfdirected learning in the digital era. Data’s were collected through interviews,participant observation, and open-ended questionnaires with respondents fromvarious countries. The findings indicate that the use of AI platforms providessignificant benefits in terms of learning time flexibility, instant feedback ongrammar and pronunciation, and increased motivation through gamification.However, several challenges were also identified, such as the limitations of AI inunderstanding complex cultural contexts, interactions that feel less human, andthe potential for technology anxiety among some learners. This study concludesthat while AI platforms are highly potential tools, their role is more optimal as asupplement to support teaching by human instructors, rather than as a completereplacement.